Brain aging and neurodegeneration: from a mitochondrial point of view. Issue 4 (14th May 2017) - Grimm, Amandine; Eckert, Anne
Abstract: Aging is defined as a progressive time‐related accumulation of changes responsible for or at least involved in the increased susceptibility to disease and death. The brain seems to be particularly sensitive to the aging process since the appearance of neurodegenerative diseases, including Alzheimer's disease, is exponential with the increasing age. Mitochondria were placed at the center of the 'free‐radical theory of aging', because these paramount organelles are not only the main producers of energy in the cells, but also to main source of reactive oxygen species. Thus, in this review, we aim to look at brain aging processes from a mitochondrial point of view by asking: (i) What happens to brain mitochondrial bioenergetics and dynamics during aging? (ii) Why is the brain so sensitive to the age‐related mitochondrial impairments? (iii) Is there a sex difference in the age‐induced mitochondrial dysfunction? Understanding mitochondrial physiology in the context of brain aging may help identify therapeutic targets against neurodegeneration. This article is part of a series "Beyond Amyloid" . Abstract : We aim to look at brain aging processes from a "mitocentric" point of view by asking: What happens to brain mitochondrial bioenergetics / dynamics during aging? Why are neurons so sensitive to the age‐related mitochondrial impairments? Are there sex differences in the age‐induced mitochondrial dysfunction? A better understanding of mitochondrial physiology may help identify therapeutic targets against neurodegeneration. This article is part of a series "Beyond Amyloid" .